Violent Crime Resulting In Serious Injury In Positive Law - Rilawadi Sahputra (Legalpreneur Journal, 2023)
This study aims to determine, assess, and analyze the rights of child victims of acts criminal persecution resulting in serious injury in Indonesia. Research methods used in this study is a normative legal research that is prescriptive. Research approach used is the law related to the legal protection of children who become victims of criminal acts of persecution that resulted in serious injuries such as The Book Of Law Criminal law, Child Protection Act, witness and Victim Protection Act, Law on juvenile criminal justice system and the Code of Criminal Procedure. Types the data used are primary data and secondary data. Data collection techniques using library study techniques. Data analysis used is a deductive analysis technique. This research concluded that the rights of children victims of abuse resulting in serious injury provided for in the Child Protection Act, The Witness and Victim Protection Act, and the juvenile justice system. But the implementation of protection of rights- rights of child victims of abuse that resulted in serious injury is still not optimal especially in the case of prosecution for damages due to criminal acts experienced by children.